2003
DOI: 10.1097/00006324-200301000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Refractive Errors in Young Myopes Using the COAS Shack-Hartmann Aberrometer

Abstract: When measuring myopes, COAS accuracy, repeatability, and instrument myopia were similar to those of the autorefractor. Error margins for both were better than the accuracy of subjective refraction. We conclude that in addition to its capability to measure higher-order aberrations, the COAS can be used as a reliable, accurate autorefractor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 26 publications
2
84
2
1
Order By: Relevance
“…There have been several other studies of wavefront measurement device reproducibility. 13,14,22 These have included the Tracey device and the WaveScan system (VISX, Santa Clara, CA, USA) as well as a method using Hartmann-Shack techniques. These studies found that the standard deviation of the conventional refractive index measured by wavefront devices was between 0.1 and 0.5D.…”
Section: Comparison Of Two Wavefront Devices D-ug Bartsch Et Almentioning
confidence: 99%
“…There have been several other studies of wavefront measurement device reproducibility. 13,14,22 These have included the Tracey device and the WaveScan system (VISX, Santa Clara, CA, USA) as well as a method using Hartmann-Shack techniques. These studies found that the standard deviation of the conventional refractive index measured by wavefront devices was between 0.1 and 0.5D.…”
Section: Comparison Of Two Wavefront Devices D-ug Bartsch Et Almentioning
confidence: 99%
“…It is important to note that in order to compare two sphero-cylinders (sphere, cylinder, and axis) one needs to transform each of them into three orthogonal refractive power vector components M, J0 and J45, where M denotes the mean spherical power while J0 and J45 describe astigmatic components at 0 and 45 degrees, respectively [21]. Since measurement errors are present both in subjective and objective assessments of vision quality, orthogonal linear regression was used to establish correlation between subjectively assessed power vector components and their objectively assessed counterparts.…”
mentioning
confidence: 99%
“…Mit dem Shack-Hartmann-Aberrometer stand für diese Arbeit ein zuverlässiges und leistungsfähiges Messgerät zur Verfügung, mit dem sich die optischen Aberrationen des menschlichen Auges gut und genau wiederholbar beschreiben lassen (Salmon et al 1998, Thibos und Hong 1999, Salmon et al 2003. Cheng et al (2003b) fanden, dass akkurates und wiederholbares Messen der Aberrationen bis vierter Ordnung mit dem COAS-Aberrometer gut möglich ist und dass Störungen der Messungen durch das Gerät selbst sehr gering sind.…”
Section: Gerätetechnologieunclassified